Mortality among US veterans with a physician-documented diagnosis of pyruvate kinase deficiency - Erin Zagadailov; Hanny Al-Samkari; Audra N. Boscoe; Bryan McGee; Sherry Shi; Dendy Macaulay; Lizheng Shi; Viviana Garcia-Horton (Hematology, 2024)
Real-world studies of pyruvate kinase (PK) deficiency and estimates of mortality are lacking. This retrospective observational study aimed to identify patients with PK deficiency and compare their overall survival (OS) to that of a matched cohort without PK deficiency. Patients with ≥1 diagnosis code related to PK deficiency were selected from the US Veterans Health Administration (VHA) database (01/1995–07/2019); patients with a physician-documented diagnosis were included (PK deficiency cohort; index: date of first diagnosis code related to PK deficiency). Patients in the PK deficiency cohort were matched 1:5 to patients from the general VHA population (non-PK deficiency cohort; index: random visit date during match’s index year). OS from index was compared between the two cohorts. Eighteen patients in the PK deficiency cohort were matched to 90 individuals in the non-PK deficiency cohort (both cohorts: mean age 57 years, 94% males; median follow-up 6.0 and 8.0 years, respectively). At follow-up, patients in the non-PK deficiency cohort had significantly longer OS than the PK deficiency cohort (median OS: 17.1 vs. 10.9 years; hazard ratio: 2.3; p = 0.0306). During their first-year post-index, 75% and 40% of the PK deficiency cohort had laboratory-confirmed anemia and iron overload, respectively. Among patients who died, cause of death was highly heterogeneous. These results highlight the increased risk of mortality and substantial clinical burden among patients with PK deficiency. While the intrinsic characteristics of the VHA database may limit the generalizability of the results, this is the first real-world study to characterize mortality in patients with PK deficiency.